EFEKTIVITAS SISTEM ONLINE SINGLE SUBMISSION (OSS) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BLORA - Yulistia Akni; Augustin Rina Herawati; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro)
Effectiveness is the concept of carrying out tasks or activities by standardizing measurements to describe the success rate of an organization in achieving worthy goals to achieve. The success of a system can be seen when all goals or objectives are achieved as previously specified. . The intended effectiveness is the Effectiveness of Online Single Submission System (OSS) in the Investment Office and One Door Integrated Service Blora regency, where the system still requires many improvements. The purpose of this research is to describe and analyze the effectiveness of attempted licensing services through the Online Single Submission (OSS) system and identify supporting factors and factors inhibiting the effectiveness of attempted licensing services through the Online Single Submission (OSS) system.This research method is qualitative descriptive. This research data collection technique is observation, interview, documentation and literature studies. Determination of subjects in this study was done using purposive sampling. The theory used is the theory of measuring effectiveness according to Kettner, Moroney, and Martin including effort (effort), cost efficiency ( cost efficiency ), results ( results ), cost effectiveness , impact ( impact ). The results of research conducted, namely licensing services through the Online Single Submission (OSS) system has not been said to be effective, because there are still some obstacles encountered. Factors supporting the effectiveness of licensing services through the Online Single Submission (OSS) system are infrastructur resources, availability of special budgets, administrative systems, budgets for system maintenance and community roles. Factors inhibiting the effectiveness of licensing services through the Online Single Submission (OSS) system are human resource limitations, limited monitoring and evaluation budgets, the community still ignores socialization, the costs incurred are not in accordance with the objectives and error system.